THE IMPACT OF TALENT MANAGEMENT PRACTICES ON EMPLOYEE PERFORMANCE: A STUDY AMONG TEACHERS IN KELANTAN - Law Chun Yang; Rogis Baker (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Nowadays, teachers are struggling to complete their daily tasks as they did not stop at only teaching the students, but they also involve in managerial activities at schools that requires specific knowledge, skills, and abilities. Furthermore, with the existence of new technology and academic syllabus within the education sector, teachers need to improve their competence to adapt with the technology and diversify their styles and method of teaching to improve the student’s result. Hence, this study had been implemented to study the factors of talent management practices that influence the employee performance among the secondary school teachers from public secondary schools in Kelantan. There were 123 teachers from SMK Kuala Krai and SMK Beris Panchor 2 who had participated in this study as the respondents. The method of quantitative research has been employed in this study which involves collecting data using questionnaires and the statistical tools used from SPSS V26.0 is descriptive analysis, inferential analysis, and multiple linear regression. The descriptive findings showed that the level of talent management practices and employee performance is found to be high among the teachers at both schools. Second, there is a positive significant relationship between the talent management practices (strategic leadership, coaching and mentoring, and competency development) with the employee performance. Meanwhile, the multiple regression analysis shows that there’s an exist and influence between talent management practices and employee performance among the secondary school teachers, while the most dominant variables in the relationship between talent management practices and employee performance are coaching and mentoring. The study findings will be used as recommendation to the board of management and teachers within the secondary schools need to be aware about these three factors that had been discussed in this study to prepare themselves for improving and sustaining the teacher’s performance through a suitable training program.